ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT KUNJUNGAN KEMBALI WISATAWAN PADA DAYA TARIK WISATA DI KABUPATEN BADUNG - Wiratini M, Ni Nyoman Ayu; Setiawan, Nyoman Djinar; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The development of the tourism sector has an impact on the increase of income per capitaand the increase of people's prosperity. The purpose of this study are 1) To analyze the influence of tourist attraction, facilities, and quality of service to the satisfaction of tourists. 2) Analyzing the influence of tourist attraction, facilities, service quality and satisfaction of tourists to the intention of returning tourists visit. 3) Analyzing the indirect influence of tourist satisfaction that mediates tourist attraction, facilities, and quality of service to the intention of returning tourists. Methods of data collection with observation, in-depth interviews and structured interviews. The data source of this research is primary data obtained from the spreading of questionnaires on 156 respondents in 4 tourist attraction which is subject to retribution, while secondary data, obtained from Badung Regency Revenue Service, Badung Regency Tourism Office, Central Bureau of Statistic (BPS) Badung Regency and Agency Central Statistics (BPS) of Bali Province. Analyzer used in this research is Path Analisys method. The results of this study indicate Attraction, Service Quality and Facilities have a positive and significant impact on Tourists Satisfaction. Tour Attractions and Travelers's Satisfaction Influence Positive and Significant to Tourist Visits Intention. Quality of Service and Facilities has a positive but insignificant effect on Tourist Visits Intention, and Tourists Satisfaction Variables is a variable that mediates the effect of Tourism Attraction, Service Quality, Facilities on Tourist Visits.